Perbandingan Kinerja dan Inovasi Material Isolator Listrik: Tinjauan Komprehensif terhadap Faktor Lingkungan, Komposisi Material, dan Metodologi Evaluatif - septiyusi, Natia nursuci; Tobuhu, Gilang; Astika putra, I Nengah dwi; Abdullah, Rafli S; Abbas, zulkarnain; Ilham, Jumiati; Hidayat, Ikhsan (Journal Of Renewable Energy Engineering, 2025)
Electrical insulators are vital components in power transmission and distribution systems. The performance of insulators is significantly influenced by environmental conditions, including humidity, pollution, and temperature, as well as their material composition. This study reviews several recent scientific publications related to the performance of ceramic, polymer, and composite insulators under various environmental conditions. The analysis indicates that environmental contamination significantly reduces insulator performance, whereas industrial and agricultural waste-based materials, such as rice husk ash (RHA) and fly ash, offer considerable potential as innovative, environmentally friendly solutions. Experimental and simulation methods play a crucial role in understanding the electrical characteristics of insulators.